Symmetries in the physics of strongly correlated electronic systems - Mancini, F.; Avella, A. (Condensed Matter Physics, 1998)
Strongly correlated electron systems require the development of new theoretical
schemes in order to describe their unusual and unexpected properties.
The usual perturbation schemes are inadequate and new concepts
must be introduced. In our scheme of calculations, the Composite Operator
Method is possible to recover through a self-consistent calculation, a
series of fundamental symmetries by choosing a suitable Hilbert space. Системи з сильною електронною кореляцією потребують розвитку нових теоретичних схем з метою опису їх незвичайних і неочікуваних властивостей. Звичайні схеми теорії збурень є неадекватні і є потреба у введенні нових концепцій. У нашому підході - Методі Композитного Оператора - є можливим відтворити в рамках самоузгодженого розрахунку ряд фундаментальних симетрій шляхом вибору відповідного гільбертового простору.